2002
DOI: 10.1080/003655902762467549
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Estrogen versus Combined Androgen Deprivation in the Treatment of Metastatic Prostatic Cancer - Scandinavian Prostatic Cancer Group (SPCG) Study No. 5

Abstract: PEP has an equal anticancer efficacy to CAD and does not increase cardiovascular mortality. Final evaluation of cardiovascular morbidity is awaiting further analysis and follow-up. PEP is considerably cheaper than CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 20 publications
2
36
0
4
Order By: Relevance
“…This finding was confirmed by a brief report of a subsequent evaluation (Hedlund et al, 2007). There was also no evidence of a difference in prostate cancer mortality in the two arms of the Mikkola trial at 2 years (RR ¼ 1.09, 95% CI: 0.40, 2.96; P ¼ 0.86) (Mikkola et al, 1998); subsequent subgroup analysis using a Cox proportional hazards model at 10-year follow-up also showed no difference in diseasespecific mortality in either M0 or M1 patients (M0: RR ¼ 1.14, 95% (Mikkola et al, 2007).…”
Section: Nature Of the Evidencesupporting
confidence: 61%
See 4 more Smart Citations
“…This finding was confirmed by a brief report of a subsequent evaluation (Hedlund et al, 2007). There was also no evidence of a difference in prostate cancer mortality in the two arms of the Mikkola trial at 2 years (RR ¼ 1.09, 95% CI: 0.40, 2.96; P ¼ 0.86) (Mikkola et al, 1998); subsequent subgroup analysis using a Cox proportional hazards model at 10-year follow-up also showed no difference in diseasespecific mortality in either M0 or M1 patients (M0: RR ¼ 1.14, 95% (Mikkola et al, 2007).…”
Section: Nature Of the Evidencesupporting
confidence: 61%
“…This finding was confirmed by a brief report of a subsequent evaluation (Hedlund et al, 2007). The Mikkola trial showed an increased level of CVS mortality in the PEP arm, although this was of borderline statistical significance (RR ¼ 2.68, 95% CI: 0.98, 7.31; P ¼ 0.05) (Mikkola et al, 1998).…”
Section: Nature Of the Evidencementioning
confidence: 65%
See 3 more Smart Citations